The Challenge of Stability and Security in West Africa - Marc, Alexandre; Verjee, Neelam; Mogaka, Stephen (Washington, DC: World Bank; and Agence Française de Développement, 2015)
This book seeks to critically examine the challenges of fragility and security in West Africa, along with the factors of resilience. It seeks to investigate key drivers of conflict and violence, and the way in which they impact the countries of the subregion. Along with emerging threats and challenges, these include the challenge of youth inclusion; migration; regional imbalances; extractives; the fragility of political institutions and managing the competition for power; security; and land. The book explores how the subregion, under the auspices of the regional organization ECOWAS has become a pioneer on the continent in terms of addressing regional challenges. This book also seeks to identify key lessons in the dynamics of resilience against political violence and civil war, drawn from countries such as Sierra Leone, Liberia, and Cote d’Ivoire that can be useful for countries around the world in the midst of similar situations. Finally, it draws on knowledge and findings from a series background papers written by leading experts, and provides insights from the perspectives of academics and development practitioners.